Looking at Arctic tourism through the lens of cultural sensitivity : ARCTISEN – a transnational baseline report - Olsen, Kjell O.; Abildgaard, Mette S.; Brattland, Camilla; Chimirri, Daniela; De Bernardi, Cecilia; Edmonds, Johnny; Grimwood, Bryan S. R.; Hurst, Chris E.; Höckert, Emily; Jaeger, Kari; Kugapi, Outi; Lemelin, R. Harvey; et al. (Umeå universitet, Arktiskt centrum vid Umeå universitet (Arcum), 2019)
ARCTISEN